Efektivitas Pelayanan Program Kartu Indonesia Sehat (KIS) di UPTD Puskesmas Manubelon Kecamatan Amfoang Barat Daya Kabupaten Kupang - Ovri Calvin Aklili; Petrus Kase; Alfred O. Ena Mau (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The results of the study showed that the accuracy of the program's targets was less effective, where there were still people who were included in the prosperous category but were KIS participants. Program socialization was considered less effective because the health center provided information through existing activities without conducting socialization to the community in general. The program's objectives were effective, where they were in accordance with the objectives of the KIS program. Program monitoring was considered less effective because there was no direct monitoring or supervision and evaluation of the KIS user community. Supporting factors for KIS program services at the Manubelon Health Center UPTD were free medical costs, while inhibiting factors were lack of information, lack of accessibility, and lack of supervision and evaluation of the Healthy Indonesia Card program.